Originally Posted by

**sgupta** Hello,

I am trying to solve this problem:

x(dy/dx)-2y=x^15

By bringing this to the standard form I get:

(dy/dx)-(2/x)y=x^14

Now I multiply the equation by (1/x^2)

I get the form d/dx(y/x^2)=(x^12)

Integrating both sides I get: (y/x^2)=((x^13)/13)+C(x^2)

Now I tried using the condition y(1)=-2 to get the value of C. However, every time I get the value of C to be 1, unfortunately this is not the right answer.

Where am I going wrong, any help would be highly appreciated.

Thanks!